2000
DOI: 10.1088/0268-1242/15/7/307
|View full text |Cite
|
Sign up to set email alerts
|

Ionization coefficients in AlxGa1-xAs (x= 0 - 0.60)

Abstract: Ionization coefficients are deduced from photomultiplication measurements on a wide range of Al x Ga 1−x As (x = 0-0.60) structures where the high-field region thicknesses vary from >1 µm down to 0.05 µm. Despite the dead space becoming an increasing fraction of the device thickness as the thickness reduces, these coefficients implicitly include its effect such that they can be used within the simple local ionization model to quantify the avalanche processes in depletion regions as thin as 0.1 µm. This success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…1 shows the typical M e and M h of layers P50, P60, P65, P70b, P80, and P90. For x<0:61, Me and M h are observed to converge as x increases, consistent with previous investigations [6]. By contrast there is a significant difference between M e and M h of the Al x Ga 10x As diodes with x 0:63.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…1 shows the typical M e and M h of layers P50, P60, P65, P70b, P80, and P90. For x<0:61, Me and M h are observed to converge as x increases, consistent with previous investigations [6]. By contrast there is a significant difference between M e and M h of the Al x Ga 10x As diodes with x 0:63.…”
Section: Methodssupporting
confidence: 91%
“…In this alloy range the electron and hole ionization coefficients, and respectively, decrease with x and the = ratio (1=k) in bulk material approaches unity as x increases [6]. By contrast, very little is known about the behavior for x>0:6.Wehave recently investigated the avalanche behavior in Al0:8Ga0:2As [8] and found that its ionization coefficients are very different in magnitude such that its / ratio deviates markedly from the trend observed in AlxGa10xAs (x 0:6).…”
Section: Introductionmentioning
confidence: 93%
“…This implies the absence of photon recycling and depletion edge movement mechanisms. As 903 Dashed lines show and for GaAs [16].…”
Section: I Onization Coefficientsmentioning
confidence: 99%
“…This is probably due to the greater inaccuracy in determining , which is lower than , and uncertainties in the absolute values of absorption coefficients. Ionization coefficients for GaAs from [16] are also plotted in Fig. 2 to highlight the contrast between the low field impact ionization in In Ga As and the conventional field dependence in GaAs.…”
Section: I Onization Coefficientsmentioning
confidence: 99%
“…4 using the parameterization for GaAs reported in Ref. 16, which was derived from McIntyre's local model assuming uniform electric field. The parameterization produces a good fit to the M e À 1 data of the GaAs diode in Fig.…”
mentioning
confidence: 99%